Efektifitas Penerapan Strategi Online Marketing Oleh UMKM Dalam Masa Pembatasan Sosial Berskala Besar (PSBB) Corona Viruses Disease 2019 (Covid-19) - Anugrah, Royan Jaluseta (Jurnal Manajemen dan Inovasi (MANOVA), 2020)
Indonesia is currently in an uproar by a dangerous virus called covid-19. Covid-19 is a virus that has a very fast transmission, so people must implement social restrictions in order to avoid covid-19 transmission. All activities that cause the crowd to do from home, including religious, economic, and educational activities. This greatly affects the daily habits of the people who are required to do online activities. The impact of covid-19 was not only felt by the community, but also felt by MSME business people. Until 2018 the total number of MSME units totaled 64.2 million throughout Indonesia and MSME had a contribution of 60.3% of the total Gross Domestic Product (GDP) of Indonesia. To be able to maintain the stability of the Indonesian economy, MSME businesses are required to prepare strategies to minimize the impact of covid-19. By changing the concept of marketing to online and utilizing special programs from the Ministry of Cooperatives and SMEs, MSME businesses will be more effective in increasing their profits.